Clinical Pharmacy Education in India- An Emerging Trend - Mishal, R H; Mishal, H B (Indian Journal of Pharmacy Practice)
Since the inception of Pharmacy education in 1937 in India, the past few decades have experienced a dramatic change in it. In 1948 the Pharmacy Council of India drafted the nation’s first standards for Pharmacy practice. The following 60 years have seen the country becoming self sufficient in Pharmaceutical production. Pharmacy profession has entered Doctors clinics and hospitals as the Clinical Pharmacists in the recent years. Clinical pharmacy has proven itself into a very promising step of patient care and service in the foreign countries. But for India it is yet a new and unexplored discipline of Pharmacy. The clinical pharmacy discipline is now taking roots in India. Some hospitals have recognized the necessity of clinical Pharmacists in their hospital set up and have started to have them in their patient care service programs. This paper intends to bring out the benefits of Clinical Pharmacy Education in Indian Pharmacy Practice.
Keywords: Clinical Pharmacy; Education; Drug Manufacturing; Pharmacy practice; Patient care.